Topping, Harvesting, and Blending Tech-niques and Cigarette Design To Reduce Nicotine Levels of Tobacco and Cigarette - JOKO HARTONO (Puslitbang Perkebunan, 2011)
Anti-smoking movement increasingly pressed towards the development of national tobacco and cigarette industry. Various regulations have been made, namely Government Regulation of Republic Indonesia (PPRI) No. 81 year 1999 and PPRI No. 38 year 2000. Previous PPRI No 19 of 2003, which among other things, deleting the provision levels of nicotine and tar content per cigarette but require cigarette manufacturers to include levels of nicotine and tar contained and push the Department of Agriculture to produce tobacco with health risks as small as possible, partly by decreasing nicotine content. Decreased levels of nicotine can be done with topping, sucker control, proper harvest, and blending, and design of cigarettes. Through proper topping and sucker control the tobacco nicotine content can be controlled. To reduce levels of nicotine, topping should not be too deep. Further, harvest should be done in stages, according to the maturity level of the leaves. Nicotine content of bottom leaves was lower compared to upper leaves. While in post-harvest technology, namely at the level of Tobacco Industry (IHT), decreased levels of nicotine can be done using certain types of tobacco on the blending process in order to obtain a mixture of nicotine content of tobacco which meets the requirement. For those big IHT greater reduction in levels of nicotine can be done through the engineering cigarette design. Keywords: Nicotiana tabaccum, a decrease of nicotine, topping, harvesting, blending, cigarette design.